دور التسويق الإلكتروني في الترويج للوجهة السياحية دراسة حالة الديوان الوطني الجزائري للسياحة ONAT - صلاح الدين،قرح; محمد،جودي (university of eloued جامعة الوادي, 2024)
إن المتتبع لما يعرفه العالم من تطورات تكنولوجية ومعلوماتية يلاحظ أن التكنولوجيا المعلومات والاتصال فرضت نفسها في كل المجالات لاسيما مجال التسويق والتسويق السياحي أو ما نسميه اليوم التسويق الإلكتروني الذي هو محور دراستنا ودوره في الترويج للوجهة السياحية، بحيث تظهر أهمية الدراسة في إبراز الدور الذي يلعبه التسويق الإلكتروني في تعريف السياح والراغبين في المعرفة أو الاستكشاف أو الترفيه من الوصول للمعلومة بسرعة وسهولة متناهية بحيث يمكن الانتقال حول العديد من الوجهات والمعالم السياحية ومعرفة تكاليف الوصول إليها وسبل التنقل بنقرة واحدة أمام الشاشة الإلكترونية، ونستخلص الهدف الرئيسي وهو استغلال المهتمين بالسياحة سواء كانوا مؤسسات خاصة أو عامة أو منظمات وطنية أو دولية بالدور الذي يلعبه التسويق الإلكتروني في الوصول إلى أكبر قدر ممكن لتحقيق الغايات من الطرفين: المستهلكين ""السياح"" والمنتجين ""وزارات السياحة، الوكالات، مؤسسات، منظمات، الديوان الوطني الجزائري للسياحة مثلا .. إلى غير ذلك""، ولمعالجة الموضوع تم إتباع المنهج الوصفي التحليلي لملائمته لموضوع الدراسة وتم من خلاله تحليل أهمية الديون وإبراز الدور الذي يلعبه في الترويج للوجهة السياحية بالاستعانة بالإمكانيات الإلكترونية، وتوصلت الدراسة إلى أن التسويق الإلكتروني يمثل ركيزة وأداة فعالة في الترويج للوجهات السياحية الوطنية منها والدولية وذلك من خلال إسقاط الدراسة على الديون الوطني الجزائري للسياحة ONAT، وأوصت الدراسة بأهمية التسويق الإلكتروني في التعريف والترويج للمعالم السياحية والأثرية والعادات والتقاليد والوجهات السياحة بصفة عامة لفعاليته واتساعه وشاسعة انتشاره وسهولة الولوج له من طرف الجميع. Anyone who follows the technological and information developments that the world knows will notice that information and communication technology has imposed itself in all fields, especially the field of marketing and tourism marketing, or what we call today e-marketing, which is the focus of our study and its role in promoting the tourist destination, so that the importance of the study appears in highlighting the role that marketing plays. The electronic system aims to introduce tourists and those wishing to know, explore, or entertain themselves to access information very quickly and easily, so that they can move around many places and landmarks and know the costs of reaching them and ways of transportation with one click in front of the electronic screen. We conclude that the main goal is to exploit those interested in tourism, whether they are private institutions , Public , national or international organizations, with the role that electronic marketing plays in reaching the greatest possible extent, achieving the goals of both parties, consumers (tourists) and producers (ministries of tourism, agencies, institutions, organizations, the Algerian National Tourism Office, for example, etc.),and to address the issue,the descriptive analytical approach was followed to suit the subject of the study, through which the importance of office was analyzed and the role it plays in promoting a tourist destination using electronic capabilities was highlighted. The study concluded that electronic marketing represents an effective pillar and tool in promoting tourist destinations, both national and international, by focusing the study on the Algerian National Tourism Office (ONAT).The study recommended the importance of electronic marketing in introducing and promoting tourist and archaeological places, customs and traditions, and tourism destinations in general, due to its effectiveness, breadth, wide spread, and ease of access by everyone.
مذكرة ماستر علوم تجارية
Keywords: marketing; e-marketing; promotion; electronic promotion; tourist destination; التسويق، التسويق الإلكتروني، الترويج، الترويج الإلكتروني، الوجهة السياحية